СИНКРЕТИЧЕСКИЙ КОРЕНЬ AĞ. - Сеидов, М. С. (Eurasian Journal of Philology Science and Education, 2015)
Language is a such social being that, it is making in the result of the social events, even nature events. All languages of the world have passed through different stages of the development and have changed since making day. Azerbaijani passed through different changings of development since making day too. There are such words in Azerbaijani they already were lost there meaning in modern times. The roots of words which were lost meaning in Azerbaijani are analysed in this work. We know that alllanguages in the world were made from the monosyllabic roots of words. Disyllabic roots of words were made from the monosyllabic roots of words too. This evemt was happened in the all languages of the world. The finding such monosyllabic roots of words and analysing their minings are our purpose. In this way we can study our native language Azerbaijani and it’sstory.